Enhancement by tetragastrin of experimental induction of gastric epithelium in the duodenum. Issue 3 (March 1989) - Tatsuta, M; Iishi, H; Yamamura, H; Yamamoto, R; Taniguchi, H
Abstract : The effects of tetragastrin and truncal vagotomy on the incidence of gastric type epithelium in the duodenum by intraduodenal instillation of 5% NaOH solution were investigated in Wistar rats. Prolonged administration of 1 mg tetragastrin/kg body weight in depot form starting one week after NaOH treatment resulted in a significant increase in gastric acid secretion and the incidence and number of villi with gastric epithelium in the duodenum in experimental week 10. Villi with gastric epithelium were found in five (23%) of 22 rats in control group, whereas abnormal villi were found in 13 (59%) of 22 rats in the tetragastrin treated group (p less than 0.05). The average number of villi with gastric epithelium rose from 0.6 (0.4) per 100 villi in control rats to 2.4 (0.6) per 100 villi in tetragastrin treated rats (p less than 0.01). On histological examination, gastric type epithelium was most often found on stunted or flattened villi, and was always within the boundaries of the area of Brunner's glands. These mucosal changes reverted toward normal with time. In week 35, the incidence of gastric epithelium was significantly less than at week 10 (p less than 0.05). In contrast, no villi with gastric epithelium were found in vagotomised rats in week 10 (p less than 0.05). Vagotomy also caused a significant decrease in gastric acid secretion. These results show that exposure of the duodenal mucosa to high levels of gastric acid enhance the induction of gastric eithelium in the duodenum.